Representation of Women's Loyalty Values in the Film Pilgrimage by Bw Purba Negara (Semiotic Analysis of Roland Barthes) - Linda Wahyuningsih (Jurnal Indonesia Sosial Teknologi, 2024)
In the 2017 Asean International Film Festival and Award, Ziarah received four awards, including Best Screenplay (BW Purba Negara), Best Actress (Ponco Sutiyem), Best Director (BW Purba Negara) and Best Film. The film is a drama genre that tells the story of a character named Mbah Sri, a 95-year-old woman who is looking for her husband (Prawiro Said) because he never came home and never even heard from him after saying goodbye to the Second Military Aggression war in 1984. The storyline is entirely based on Mbah Sri as the heir to the memory of the historical events experienced by her husband. This study uses a qualitative approach using Roland Barthes' semiotic analysis. Semiotic analysis is a way or method to analyze and give meanings to symbols that contain a package of symbols, symbols, messages or textsThis research uses a qualitative approach using Roland Barthes' semiotic analysis. In conclusion, the representation of women's loyalty values in the film Ziarah by BW Purba Negara is depicted through the actions and characteristics of couples who are still loyal even though their partners have no news. Mbah Sri still thinks about her partner and tries to find her again at all costs. He did not give up on the search process until he finally rediscovered his true love in his old age.